The Use of Computed Tomography in Fragmented Coronoid Disease: A Case Report - Braden, T. D.; Stickle, R. L.; Dejardin, L. M.; Mostosky, U. V. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
A 13-month-old Rottweiler was presented with a lameness on the left front leg. The CT scan revealed a large fragmented coronoid process in the elbow joint which was not demonstrable on regular radiographs.
Keywords: Computed tomography; fragmented coronoid process; dog